The Surgical Timing and Prognoses of Elderly Patients with Hip Fractures: A Retrospective Analysis - Sun L; Wang C; Zhang M; Li X; Zhao B (Clinical Interventions in Aging, 2023)
Lili Sun, Cong Wang, Mingqing Zhang, Xiang Li, Bin Zhao Department of Emergency, Beijing Jishuitan Hospital, Beijing, People’s Republic of ChinaCorrespondence: Bin Zhao, Department of Emergency, Beijing Jishuitan Hospital, No. 31 of Xinjiekou East Street, Xicheng District, Beijing, 100035, People’s Republic of China, Tel +86-1058516417, Fax +86-1058516931, Email binzhao1492@163.comBackground: Guidelines exist for the surgical treatment of hip fractures, but the association between the surgical timing and the incidence of postoperative complications and other important outcomes in elderly patients with hip fracture remains controversial.Objective: This study aims to explore the association between the surgical timing and the prognoses in elderly patients with hip fracture.Methods: A total of 701 elderly patients (age ≥ 65 years) with hip fractures who were treated in our hospital from June 2020 to June 2021 were selected. Patients who underwent surgery within 2 d of admission were assigned to the early surgery group, and those who underwent surgery after 2 d of admission were assigned to the delayed surgery group. The prognosis indices of the patients in the two groups were recorded and compared.Results: The length of postoperative hospitalisation in the early surgery group was significantly lower than that in the delayed surgery group (P < 0.001). The European quality of life questionnaire (EQ-5D) utility in the delayed surgery group was significantly lower than that in the early surgery group at 30 days and 6 months after operation (P< 0.05). Compared with the delayed surgery group, the incidence of pulmonary infection, urinary tract infection (UTI) and deep vein thrombosis (DVT) in the early surgery group were significantly lower. There were no significant differences between the two groups in terms of mortality and excellent rates of the HHS at six months after the operation. In addition, the early surgery group had a lower readmission rate than the delayed surgery group [34 (9.5%) vs 56 (16.3%), P = 0.008].Conclusion: Earlier surgery can reduce the incidence of pulmonary infections, UTI, DVT and readmission rate among elderly patients with hip fractures, shorten postoperative hospitalisation.Keywords: Hip fracture, elderly patients, timing of surgery, prognosis